The problem of osteoarthritis of the knee joint and running through the prism of magnetic resonance tomography - A. V. Snigireva; S. M. Noskov; A. A. Lavruchina (National Electronic Information Consortium (NEICON), 2020)
The number of women and the elderly has now increased among marathon runners. This cohort has a high risk of osteoarthritis development. The hypothesis, based on little scientific evidence, is that the additional stress on knee joints that occurs during long running can potentially lead to damage to joint structures and osteoarthritis development. The review presents modern generalized data on magnetic resonance imaging (MRI) of knee joints in long-distance runners. Special attention is paid to the syndrome of fluid increase in subchondral bone, which is determined by increasing the signal intensity in T2-weighted images (decrease in T1-weighted images), called bone marrow oedema (BMO). Classification and pathogenetic variants of BMO development (theory of intrusion and contusion) are presented. Particular cases of BMO development in marathon runners are considered. The dynamics of BMO in different time intervals after the races in beginners and professional marathon runners is described. Changes in MRI images of knee cartilage after running on the treadmill in healthy women and in women suffering from osteoarthritis are shown. A comparison of the frequency of osteoarthritis of knee joints in runners compared to footballers and weightlifters was made. The conclusion was made on the preventive effect of long walking and running (at least 12.5 km/week), including marathon distances, on the development and progression of osteoarthritis of knee joints.